Legal Boundaries between Criticism and Defamation - Salsabilla, Salisah (Siber International Journal of Advanced Law (SIJAL), 2025)
This article discusses the legal boundaries between legitimate criticism and defamation in the context of Indonesian law. The study uses a normative method with a statutory, case, and conceptual approach, examining provisions in the Criminal Code, the ITE Law, and relevant jurisprudence. The results of the study show that although freedom of speech is guaranteed in the constitution, its implementation still often conflicts with criminal provisions on defamation. Criticism delivered in good faith, based on facts, and in the public interest should not be criminalized. However, the multiple interpretations of the related articles often lead to the criminalization of legitimate criticism. This article emphasizes the importance of legal reform and the establishment of technical guidelines so that the boundaries between criticism and defamation become clearer, so that freedom of speech remains guaranteed without ignoring the right to a good name.